Spesies Padi Liar (Oryzaspp.) Sebagai Sumber Gen Ketahanan Cekaman Abiotik Dan Biotik Pada Padi Budi Daya - Tintin Suhartini (Jurnal Penelitian dan Pengembangan Pertanian, 2016)
ABSTRACTWild rice species could be used  for improvement of rice varieties because they have a good character for resistance to biotic and abiotic stresses. Some of Indonesian wild rice species are Oryza meyeriana, O. granulata, O. longiglumis, O. officinalis, O. ridleyi, O. rufipogon and O. schlechteri. IRRI has a collection of 2,500 accesions of wild rice and 18 species were collected in ICABIOGRAD, Bogor. Some species of wild rice are known to have resistance genes to biotic and abiotic stresses. A number ofaccessions of O.  officinalis contained resistance gene to brown planthopper, blast disease, bacterial leaf blight (BLB) and sheath rot. One of the species that has resistance to pests and diseases is O. minuta. The resistance to tungro virus occurs in O. punctata. Tolerance to drought, Al and Fe toxicities occurs in wild rice species of O. sativa genome AA group. Resistance genes from wild rice species can be inserted into cultivated rice through conventional techniques in combination with biotechnology, while gene transfer and gene detection from wild rice to cultivated rice can be done through cross breeding, molecular markers, backcrossing and embryo rescue. The success of introgression of resistance genes from wild rice species to cultivated rice will increase genetic diversity of rice. As an example O. minuta has been implemented in introgression of BLB resistance gene on IR64. Introgression of O. nivara gene in IRRI had improved some superior rice varieties in Indonesia, namely IR30, IR32, IR34, IR36 and IR38, which were tolerant to brown planthopper, dwarf virus and bacterial leaf blight. Oryza rufipogon wich has BLB and blast resistance gene has been used for improvement of new varieties Inpari Blas and Inpari HDB which were released in 2013.Keywords: Oryza spp., varietal improvement, resistance genes, biotic stresses, abiotic stressesAbstrakSpesies padi liar dapat dimanfaatkan dalam perakitan varietas unggul karena memiliki gen ketahanan terhadap cekaman biotik dan abiotik. Spesies padi liar yang ada di Indonesia adalah Oryza meyeriana, O. granulata, O. longiglumis, O. officinalis, O. ridleyi, O. rufipogon, dan O. schlechteri. IRRI memiliki koleksi 2.500 aksesi padi liar dan 18 spesies dikoleksi di BB Biogen. Sejumlah aksesi O. officinalis memiliki gen ketahanan terhadap wereng coklat, penyakit blas, hawar daun bakteri (HDB), dan busuk pelepah. Salah satu spesies yang memiliki ketahanan terhadap hama-penyakit tersebut adalah O. minuta. Ketahanan terhadap virus tungro terdapat pada O. punctata. Toleransi terhadap kekeringan, keracunan Al, dan Fe terdapat pada spesies padi liar kelompok O. sativa genom AA. Gen ketahanan dari spesies padi liar dapat dimasukkan (introgresi) ke dalam padi budi daya melalui teknik konvensional yang dikombinasikan dengan bioteknologi, sementara transfer gen dapat melalui persilangan, marka molekuler, silang balik, dan penyelamatan embrio. Keberhasilan introgresi gen ketahanan dari spesies padi liar ke padi budi daya akan meningkatkan keragaman genetik tanaman. Spesies padi liar O. minuta telah dimanfaatkan dalam introgresi gen ketahanan HDB pada varietas IR64. Introgresi gen asal O. nivara di IRRI menambah varietas unggul di Indonesia, yaitu IR30, IR32, IR34, IR36, dan IR38, yang toleran terhadap wereng coklat, virus kerdil rumput, dan HDB. Spesies padi liar O. rufipogon yang memiliki gen ketahanan HDB dan blas telah digunakan dalam pembentukan varietas unggul baru Inpari HDB dan Inpari Blas yang dilepas pada 2013.